Reflexões em biologia da conservação - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2018)
Conservation biology has been taught in postgraduate courses at the Museu Paraense Emílio Goeldi since 1997. Over the years, students have produced monographs and final papers for the discipline, serving the academic circuit. The biology discipline arose from the idea of ​​going beyond the “academic walls” and transforming these papers into articles for dissemination, in order to share with society the reflections produced in the classroom, which point to several issues that concern society as a whole and present, in the light of scientific knowledge, ideas and suggestions that can expand actions to conserve biodiversity and intensify the debate between academia and society in relation to these issues.
Reflections on conservation biology
Keywords: Biologia da Conservação; Ambiente urbano - conservação; Desafios; CNPQ::CIENCIAS BIOLOGICAS::ECOLOGIA